Perioperative factors contributing to delayed return of continence after radical prostatectomy: The role of race and comorbidities - Divya Ajay; Hanhan Li; Brittani Barrett-Harlow; Jenny Nguyen; Cooper Benson; Xuemei Wang; Brian F. Chapin; John Davis; O. Lenaine Westney (Continence, 2022)
Objective:: To characterize factors that contribute to a delay in regaining continence after robot-assisted laparoscopic prostatectomy (RALP) at a single tertiary cancer center. Subjects and methods:: In a retrospective analysis of patients with pathologically proven prostate cancer treated by two surgeons with a curative intent, patient demographics, operative details, and postoperative continence were extracted from the electronic medical record. Time to dry was defined as the time interval between the date of prostatectomy and the first evaluation at which patients present with zero pad use. Patients were evaluated for pad usage at four time points. All statistical analyses were conducted in SAS and Splus. Results:: From 2008 to 2015, 1275 patients were analyzed. The median follow-up time was 32 (19–48) months. Univariate analysis demonstrated that older age at RALP (HR 0.98, p<0.01), race (HR 0.77, p 0.04), clinical (HR 0.84, p 0.02) and pathologic stage (HR 0.85, p 0.02), nerve-sparing status (HR 1.64, p<0.01) and number of comorbidities.